Evaluation of molecular diversity of ex situ conserved germplasm of palmyrah (Borassus flabellifer L.) accessions using RAPD markers - K.T. Venkataramana, Jiji George,; M.K. Rajesh, P. Nainar; Karun, Anitha (Journal of Plantation Crops, 2016)
The genetic relationship of 96 palmyrah palms, consisting of 24 indigenous accessions from Tamil Nadu and Andhra Pradesh, was investigated using Random Amplified Polymorphic DNA (RAPD) markers. Hundred and eighty primers were used initially to identify the polymorphic primers in six random samples and 10 polymorphic primers were selected to amplify the 96 palms. These 10 primers produced a total of 112 reproducible bands and out of them, 41 fragments (36.6 %) showed polymorphism.Â The number of bands produced with each primer varied from seven to 15 with an average of 11.2 bands per primer.Â The percent polymorphism ranged from 7.7 to 71.4 with an average of 37.4 per cent when all the primers were taken collectively.Â UPGMA grouped all the accessions into two major clusters at 0.85 similarity value. The highest similarity value (0.96) was observed between the accessions KLKM-8 and THY-54 and the lowest similarity value (0.782) was obtained between ANBI-17 and RCML-11. The relatively low polymorphism suggests a narrow genetic diversity of palmyrah populations from which the present accessions have been derived and maintained over the years.